Physiological, genetic, and pathogenetic variability in Macrophomina phaseolina, the causal agent of charcoal rot - De los Santos, Berta; Aguado, A; Aparicio Durán, L. (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2017)
Motivation: Macrophomina phaseolina (Tassi) Goidanich is a primarily soilborne pathogen with a wide distribution, varied host range, great longevity and high competitive saprophytic ability (Babu et al., 2010). About 500 plant diseases are caused by this fungus (Su et al., 2001), and it is often termed ‘charcoal rot’. Charcoal rot has emerged as an important disease in strawberry production systems that have abandoned soil fumigation with methyl bromide (Mertely et al., 2005; Zveibil and Freeman, 2005; Aviles et al., 2008). Although, only one species (M. phaseolina) is recognized within the genus Macrophomina (Sutton, 1980), the high levels of morphological variability of M. phaseolina across different hosts and geographical regions suggest that this species may be divided into subgroups (Aboshosha et al., 2007; Beas-Fernández et al., 2006; Hawatema y Hameed, 2006; Karunanithi et al., 1999; Mayek-Pérez et al., 1997; Mihail y Taylor, 1995; Omar et al., 2007). This work aimed to study the population structure of M. phaseolina associated with strawberry crop in Huelva, and to characterize the isolates with respect to in vitro growth rate, genotypic variability, and pathogenicity to strawberry plants. Methods and results: Twenty two isolates of M. phaseolina from strawberry, blueberry, watermelon and rice are tested in this work. The morphological characteristics of the isolates are investigated, including colony phenotype on medium containing 120 mM potassium chlorate (Pearson et al., 1986), and relative growth rate at different temperatures and pH (Beas-Fernandez et al., 2006; Mayek-Perez et al., 1997). Pathogenicity test are carried out under controlled conditions. Mono-sclerotic cultures of the fungus were obtained for molecular characterization.